Foreign Direct Investments and Their Impacts to Environment, Albania Case - Rembeci, Godiva (European Journal of Economics and Business Studies, 2017)
FDI is considered as positive factor on economic growth for the hosting country, because of its contribution to the employment growth, productivity, income, transfer of know-how, export promotion of its products in international market, etc. Especially in transition economies FDI compare to other the external flows is an important source for financing the current account deficit and in addition those flows are preferable because do not create debts for the hosting country. So far, the economic impacts of FDIs are almost well measured, but their impacts in other aspects such as environmental or social ones, are less recognizable and measured. By this paper the author aim to measure the share of foreign direct investments in pollution intense industries and their impacts to Albanian environment. The subject of the analysis is the FDI stock by economic activities focusing mostly to those activities determined by OECD as pollution-intensive industries, for the period 2007-2014. Both EUROSTAT and national statistical data produced by Bank of Albania are used to calculate the share of foreign investors’ involvement in pollution-intensive activities. The results show that in Albania, the FDI stock in pollution intense activities has an considerable position on the total FDI stock and its level of participation is higher compare to the EU figures
Keywords: FDI stock, environment, pollution intensive industries, EUROSTAT, Bank of Albania